Visuo-manual coordination in preterm infants without neurological impairments - Petkovic, Maja; Chokron, Sylvie; Fagard, Jacqueline (Research in developmental disabilities, 2016)
The extent of and reasons for visuo-manual coordination deficits in moderate and late preterm born infants without neurological impairments are not well known. This paper presents a longitudinal study on the visuo-manual development of twelve preterm infants, born after 33–36 weeks of gestation without neurological complications, between the ages of 6 and 12 months. Visuo-manual integration and grasping were assessed using the Peabody Developmental Motor Scales, along with bimanual coordination and handedness tests. Visual function was examined once prior to the beginning of the study. Gross motor development was also evaluated every month. Preterm infants were compared to a control group of ten full-term infants according to corrected age. Compared to full-terms, the visual perception of preterm infants was close to normal, with only a measure of visual fixation lower than in full-terms. In contrast, preterm infants had delayed development of visuo-manual integration, grasping, bimanual coordination, and handedness even when compared using corrected age. Tonicity and gestational age at birth were the main variables associated to the delays. These results are discussed in terms of the possible factors underlying such delays. They need to be confirmed on a larger sample of preterm born children, and to be correlated with later development. This would allow developing markers of future neuropsychological impairments during childhood.